Pelatihan Digital Marketing Berbasis AI sebagai Bentuk Pemerataan Teknologi di Pulau Batam, Kepulauan Riau - Zainal Abidin Achmad; Ahmad Ilham Ramadhan Kalis; Devina Setya Vanessa; Desi Tri Wahyuningsih (Fakultas Teknik Universitas Cenderawasih, 2024)
Batam City as a center of industry and trade has a large market The city of Batam, as an industrial and trade hub, holds significant market potential for the utilization of digital technology. While Batam has established infrastructure that facilitates inter-island access, digital transformation has yet to reach the smaller surrounding islands. The application of Artificial Intelligence (AI) remains relatively unfamiliar to many communities on islands outside Batam. The objective of this training, organized by the student boarding school of UPN Veteran East Java, is to provide an in-depth understanding of digitalization and AI concepts in digital marketing as a means to support the economy of Batam Island’s communities. This Community Service Program (PKM) is implemented through socialization on AI concepts, the positive potential impacts of AI, and practical AI application workshops, in collaboration with the Director of the SPMAA Batam Foundation and ICT volunteers. The results of this PKM activity indicate a high level of enthusiasm among the community to learn about AI concepts and their use in marketing products on social media. Through this training, it is expected that MSME owners and the entire community on Batam Island will benefit from technological advancements, particularly AI, and that it will support the government’s efforts in promoting equitable digital transformation across Batam Island.